87Sr/86Sr dating and preliminary interpretation of magnetic susceptibility logs of giant piston cores from the Rio Grande Rise in the South Atlantic. (December 2017) - Lacasse, Christian Michel; Santos, Roberto Ventura; Dantas, Elton Luiz; Vigneron, Quentin; de Sousa, Isabela Moreno Cordeiro; Harlamov, Vadim; Lisniowski, Maria Aline; Pessanha, Ivo Bruno Machado; Frazão, Eugênio Pires; Cavalcanti, José Adilson Dias
Abstract: Giant piston cores recovered from shallow depths (<1200 mbsl) on the northern flank of the Rio Grande Rise, bathed today in intermediate waters (AAIW, UCDW), have uncovered new stratigraphic and paleoceanographic aspects of the Plio-Pleistocene in the South Atlantic. Based on strontium isotope analysis of well-preserved foraminifera-rich sediment a stratigraphy was developed from lowess curve fitting of the data and an optimized matching with an internationally recognized timescale of 87 Sr/ 86 Sr seawater variation through geological times. Depth-to-age conversion of the magnetic susceptibility logs was implemented based on the identification of correlative peaks between cores and the developed 87 Sr/ 86 Sr age model. The influence of Northern Hemisphere glaciation is reflected in these new stratigraphic logs by a gradual increase from ∼2.7 Ma in the lower signal of magnetic susceptibility (below background level), to values approaching the arithmetic means, likely reflecting an overall increase in terrigenous input. The Rio Grande Rise cores have very low Plio-Pleistocene sedimentation rates (∼0.4–0.8 cm/ka), similar to gravity cores from the oligotrophic subtropical South Atlantic (below ∼2000 mbsl), and for which an inverse correlation between carbonate content and magnetic susceptibility was established. The coring depths on the Rio Grande Rise encompass strong gradients in oxygen concentration and other seawater parameters that define today's AAIW/UCDW transition. Depth-dependent variation in sedimentation rates since the onset of Northern Hemisphere glaciation coincides with the incursion of intermediate waters (UCDW, AAIW) in response to the overall reduction of NADW export to the Southern Ocean. Background levels of magnetic susceptibility in the cores suggest that this variation is mainly attributed to terrigenous input. The source region of this material has yet to be traced by considering in particular the mineral composition and paramagnetic properties of the detrital clays. Highlights: Foraminifera-rich sediments in RGR giant piston cores were dated by 87 Sr/ 86 Sr. Influence of NH glaciation is reflected in the RGR magnetic susceptibility logs. Variation in Plio-Pleistocene sedimentation rates on RGR is water depth dependent. This variation is mainly terrigenous and coincides with an overall NADW reduction. Given path to UCDW incursion led to increased input of paramagnetic clay minerals.